Clinical Study of De novo Histoid Leprosy - H Bangaru; Seema Afreen Kazi (Clinical Dermatology Review)
Histoid leprosy is an uncommon variant of lepromatous leprosy with a unique clinical presentation with asymptomatic multiple, discrete, shiny, dome-shaped skin-colored to erythematous papules and nodules seen over the face, trunk, extremities, histopathological findings, and a characteristic bacterial morphology that usually follows treatment failure especially after dapsone monotherapy. Occasionally, it occurs de novo without any history of previous inadequate or irregular treatment. In this study, we present a total of 8 cases of histoid leprosy with their clinical and histopathological findings. Eight cases of histoid leprosy coming to the outpatient department were enrolled after taking written informed consent. Clinical and histopathological characterization of histoid leprosy. We present a clinical study of clinical, histopathological, and bacteriological features of eight patients with histoid leprosy. The highly bacilliferous, though less common, histoid variant of lepromatous leprosy is increasingly occurring de novo. A probable reason may be due to primary dapsone resistance by the folP1 gene, and another possibility could be due to other mutations in the Mycobacterium leprae. Early recognition of de novo cases with prompt institution of sufficient duration of WHO multibacillary multidrug therapy therapy under prolonged follow-up is important to ensure a favorable outcome.